The Italian contributions to the history of salicylates - Giampiero Pasero; Piero Marson (PAGEPress Publications, 2011)
It is well-known that the modern history of salicylates began in 1899 when the compound acetylsalicylic acid was registered and introduced commercially as "aspirin" by the Bayer Company of Germany. As a matter of fact, however, remedies made from willow bark had been used to treat fever and rheumatic complaints at least since 1763, when Edward Stone described their efficacy against malarian fever. A number of Italian scientists made significant contributions during the long period of research leading up to the synthesis of acetylsalicylic acid and its widespread use in rheumatic diseases. In this paper we will review the contributions of some of these researchers, beginning with Bartolomeo Rigatelli, who in 1824 used a willow bark extract as a therapeutic agent, denominating it "salino amarissimo antifebbrile" (very bitter antipyretic salt). In the same year, Francesco Fontana described this natural compound, giving it the name "salicina" (salicin). Two other Italian chemists added considerably to current knowledge of the salicylates: Raffaele Piria in 1838, while working as a research fellow in Paris, extracted the chemical compound salicylic acid, and Cesare Bertagnini in 1855 published a detailed description of the classic adverse event associated with salicylate overdoses - tinnitus - which he studied by deliberately ingesting excessive doses himself. Bertagnini and above all Piria also played conspicuous roles in the history of Italy during the period of the Italian Risorgimento, participating as volunteers in the crucial battle of Curtatone and Montanara during the first Italian War of Independence.